Public Transport Integration Challenges of Wira Wiri Suroboyo as a Commuter Train Feeder - Susanti, Anita; Supriyatno, Dadang; Dermawan, Dodik Arwin; Wibisono, R. Endro (IPTEK, DRPM, Institut Teknologi Sepuluh Nopember, 2024)
Congestion is a problem in most big cities, including Surabaya. One alternative to reduce congestion is to create city transportation with excellent service. Surabaya has had city transportation, city buses and also commuter trains for a long time. However, it is considered that travelers do not have excellent service. In 2023, a new city transportation will be created with the name Wira Wiri Suroboyo (WWS) with the aim of diverting some private vehicle users toWWS. However, until now,WWS has not been able to attract the interest of the public who use private vehicles. So it is necessary to research the operational performance of theWWS and analyze integration opportunities with commuter trains. The research method used was conducting field surveys and interviews with WWS passengers. The results of the survey show that load factor, headway, departure frequency, number of vehicles in operation are still not optimal to divert private vehicle users toWWS and at the same time integrate with commuter trains. Therefore, other efforts are needed to limit private vehicles in order to provide cross-subsidies for public transportation. So that it does not burden operational costs which have been borne by the Government.